Approximate solutions and scalarization in set-valued optimization. (2nd November 2017) - Dhingra, Mansi; Lalitha, C. S.
Abstract: Certain notions of approximate weak efficient solutions are considered for a set-valued optimization problem based on vector and set criteria approaches. For approximate solutions based on the vector approach, a characterization is provided in terms of an extended Gerstewitz's function. For the set approach case, two notions of approximate weak efficient solutions are introduced using a lower and an upper quasi order relations for sets and further compactness and stability aspects are discussed for these approximate solutions. Existence and scalarization using a generalized Gerstewitz's function are also established for approximate solutions, based on the lower set order relation.